The Status of Electronic Journals in India from 2006-2015 - A Brief Study - Satynarayana, D. (Journal of Information and Knowledge, 2018)
Electronic journals in India have grown exponentially. The aim of this work is to examine the nature and growth of electronic journals that have been assigned ISSN from 2006 to 2015 by National Science Library, New Delhi. It covers a total of 5979 electronic journals with assigned ISSN.